Developmental Wiring of Specific Neurons Is Regulated by RET-1/Nogo-A in Caenorhabditis elegans. Issue 1 (1st January 2017) - Torpe, Nanna; Nørgaard, Steffen; Høye, Anette M; Pocock, Roger
Abstract: Nogo-A is a membrane-bound protein that functions to inhibit neuronal migration, adhesion, and neurite outgrowth during development. In the mature nervous system, Nogo-A stabilizes neuronal wiring to inhibit neuronal plasticity and regeneration after injury. Here, we show that RET-1, the sole Nogo-A homolog in Caenorhabditis elegans, is required to control developmental wiring of a specific subset of neurons. In ret-1 deletion mutant animals, specific ventral nerve cord axons are misguided where they fail to respect the ventral midline boundary. We found that ret-1 is expressed in multiple neurons during development, and, through mosaic analysis, showed that ret-1 controls axon guidance in a cell-autonomous manner. Finally, as in mammals, ret-1 regulates ephrin expression, and dysregulation of the ephrin ligand VAB-2 is partially responsible for the ret-1 mutant axonal defects. Together, our data present a previously unidentified function for RET-1 in the nervous system of C. elegans .